Evaluation of physico-mechanical characteristics of cashew nut shell liquid-epoxy composites with Borassus and Tamarind fruit fibres as reinforcements. Issue 3 (3rd April 2019) - Nayak, Suhas Yeshwant; Shenoy Heckadka, Srinivas; Thomas, Linto George
ABSTRACT: In this study, Cashew Nut Shell Liquid (CNSL)-epoxy matrix-based composites reinforced with borassus and tamarind fibres were fabricated using compression moulding technique. Three different types of composites were fabricated, namely Borassus fruit fine fibre/CNSL-epoxy composites (BF composites), Tamarind fibre/CNSL-epoxy composites (TF composites) and Tamarind/Borassus fruit fine fibre CNSL-epoxy hybrid composites (HB composites). In addition, CNSL-epoxy neat polymer was also fabricated for comparison. Physical properties such as micro-hardness, void percentage, and mechanical properties like tensile, flexural, Interlaminar Shear Strength (ILSS), and impact strength were investigated. Scanning Electron Microscope (SEM) was used to study the failure mechanism of the composites. Experimental results indicate that tensile and flexural properties of BF composites were higher when compared to TF and HB composites. Micro-hardness and impact strength of HB composites were better than the others. SEM images indicated better fibre-matrix bonding in BF composites indicating improved resistance to delamination. Thus, borassus and tamarind fibre reinforced CNSL-epoxy composites can be used as an alternative material for light to moderately loaded structural engineering applications.